Pengaruh Leader Member Exchange Terhadap Kepuasan Kerja Karyawan - Rizka Nurhasti Agusta Harahap; Sholihati Amalia (Jurnal Riset Bisnis dan Investasi, 2017)
This research aims to determine the influence of leader member exchange to employee job satisfaction in PT Sandy Globalindo. Leader-member exchange is variable (X) and job satisfaction is a variable (Y). The research method that used is the analytic method with cross sectional approach. The sample in this research is 101 employees. Descriptive analysis showed that the leader-member exchange in PT Sandy Globalindo in the category enough with a mean of 2.91 and job satisfaction of employees at PT Sandy Globalindo in the category enough with a mean of 3.04. Simple linear regression test results indicate that the variable leader-member exchange impact of 38.2% on job satisfaction while amounting to 61.8% of job satisfaction influenced by other things that are not explained in this research. Therefore, it can be concluded that there is a significant influence of leader-member exchange to employee job satisfaction in PT Sandy Globalindo.